Analisis Efektivitas Eduaide.ai dalam Membantu Persiapan Pembelajaran pada Siswa Kelas 9 - Maulida, Rusyda; Muchlis (Jurnal Teknik Informatika, 2025)
This research aims to analyze the effectiveness of using Eduaide.ai in assisting learning preparation for 9th grade students. This study employs an experimental method by comparing student learning outcomes through pre-test and post-test in two conditions: manual learning preparation and learning preparation with the assistance of Eduaide.ai. The research sample consists of 9th grade students who will be tested on their abilities before and after using the learning platform. The collected data will be analyzed quantitatively to measure the platform's effectiveness in improving student learning outcomes. The results of this research are expected to provide insights into the benefits of using artificial intelligence technology in supporting students' learning preparation processes